Comparison of Healing Time in Closed Fractures of the Tibial Diaphysis and Tibial-Fibula after ORIF Plate and Screw at Waled Regional Public Hospital, Indonesia - Sakinah, Dede Nurlaela; Putro, Widiyatmiko Arifin; Debyanti, Merliana (GHMJ (Global Health Management Journal), 2025)
Background: Fractures are projected to become the fourth leading cause of death by 2030. A fracture is a discontinuity in the bone that is often accompanied by damage to the surrounding tissues. The healing process of fractures is influenced by various factors, the greater the damage to the bone and surrounding tissues, the longer the healing time. In cases of tibia and fibula fractures, the most commonly used surgical procedure in Indonesia is Open Reduction and Internal Fixation (ORIF) using Plates and Screw. Aims: To compare of healing time in closed fractures of the tibial diaphysis and tibial-fibula after ORIF Plate and Screw at Waled regional public hospital. Methods: This research uses a cross sectional design. A total of 77 samples were obtained using total sampling. Statistical tests use Mann Whitney. Results: There were 37 patients with closed fractures of the tibia diaphysis and 40 patients with closed fractures of the tibia-fibula diaphysis. The healing time for closed tibial diaphyseal fractures was ≤ 24 weeks in 12 patients (32.4%), while > 24 weeks was 25 patients (67.6%). In patients with closed fractures of the tibia-fibula diaphysis within ≤ 24 weeks and > 24 weeks, the number was the same, namely 20 patients (50.0%). In the Mann-Whitney test, a significance value of 0.032 (p<0.05) was obtained, indicating a significant difference in the healing time between closed fractures of the tibial diaphysis and tibia-fibula after ORIF Plate and Screw at Waled Regional Hospital, with an average healing of 44.69 weeks for closed fractures of the tibial diaphysis, whereas for fractures closed tibia-fibula diaphysis 33.74 weeks.   Conclusion: The average healing time for closed tibial diaphyseal fractures is longer than for tibia-fibula.